A case report of primary para-testicular spindle cell rhabdomyosarcoma - Su, Peng; Yang, Ying; Wang, Xiaomin; Chen, Shulian; Zhang, Neng; Yang, Hua (Frontiers in Oncology, 2023)
Para-testicular Rhabdomyosarcoma (PTRMS) is a rare tumor, and it accounts for 7% of all rhabdomyosarcoma tumors. Among all the rhabdomyosarcoma (RMS), the spindle cell RMS are extremely rare. The present study describes a case of a para-testicular spindle cell RMS that was treated with a radical inguinal orchiectomy (RIO) and right scrotal resection. A 17-year-old male presented with a half-year history of a rapidly growing, painless, right scrotal mass. His CT of pelvic cavity showed a mixed density mass in the right scrotum and the maximum cross-sectional area was about 76.5mm × 64.5mm. An X-ray of the chest demonstrated no evidence of metastasis and a local surgical excision was performed subsequently. The histopathological and immunohistochemical examination confirmed the final diagnosis of spindle cell RMS. As a newly diagnosed case, strict and regular follow-up is needed. This article focuses on the importance of prompt recognition, diagnosis, pathological features and appropriate management of para-testicular spindle cell RMS.